Changes in the gut microbiota of forest musk deer (Moschus berezovskii) during ex situ conservation - Jiang, Yuanlin; Han, Xiangyu; Li, Mengqi; Feng, Nuannuan; Yang, Pengcheng; Zhao, Haoxi; Zhang, Chenxi; Shi, Minghui; Huang, Zhixin; Sun, Rubin; Liu, Shuqiang; Hu, Defu (Frontiers in Microbiology, 2022)
Ex situ conservation is an important technique for protecting rare and endangered wildlife, and maintaining stable individual health is crucial to its success. Gut microbiota composition is a critical indicator of animal health and should therefore be closely monitored during ex situ conservation to track impacts on animal health. Forest musk deer (Moschus berezovskii) were historically distributed in Hebei Province, China, however, they are now extinct in the region. Thus, ex situ conservation efforts were conducted in 2016 whereby approximately 50 individuals were artificially migrated from Weinan, Shaanxi to Huailai, Hebei. To monitor gut health of these migrated individuals, we used 16S rRNA high-throughput sequencing technology to examine the microbiota differences between Huailai juvenile and Weinan juvenile groups, and between Huailai adult and Weinan adult groups. Alpha diversity analysis indicated that the richness of microbiota significantly decreased after migration to the Huailai area, and the beta diversity results also showed significant dissimilarity in gut microbial communities, demonstrating the distinct microbial structure differences in the forest musk deer population from the two areas, for both juvenile and adult groups, respectively. In addition, PICRUSt functional profile prediction indicated that the functions of gut digestion and absorption, and degradation of toxic substances were significantly weakened after ex situ conservation. Differences in diet composition between the individuals of the two sites were also observed and the impact of food on gut microbiota compositions within forest musk deer during ex situ conservation was investigated. This study provides a theoretical basis for developing ex situ conservation measures, especially for the protection of forest musk deer.